The value of cardiac magnetic resonance post-contrast T1 mapping in improving the evaluation of myocardial infarction - Xiang, Chunlin; Zhang, Hongyan; Li, Haojie; Zhou, Xiaoyue; Huang, Lu; Xia, Liming (Frontiers in Cardiovascular Medicine, 2023)
Objective To explore the additional value of cardiac magnetic resonance (CMR) post-contrast T1 mapping in the detection of myocardial infarction, compared with late gadolinium enhancement (LGE). Materials and methods A CMR database of consecutive patients with myocardial infarction was retrospectively analyzed. All patients were scanned at 3 T magnetic resonance; they underwent conventional CMR (including LGE) and post-contrast T1 mapping imaging. Two radiologists interpreted the CMR images using a 16-segment model. The first interpretation included only LGE images. After 30 days, the same radiologists performed a second analysis of random LGE images, with the addition of post-contrast T1 mapping images. Images were analyzed to diagnose myocardial scars, and the transmural extent of each scar was visually evaluated. Diagnoses retained after LGE were compared with diagnoses retained after the addition of post-contrast T1 mapping. Results In total, 80 patients (1,280 myocardial segments) were included in the final analysis. After the addition of post-contrast T1 mapping, eight previously unidentified subendocardial scars were detected. Compared with LGE images, the percentage of infarcted segments was higher after the addition of post-contrast T1 mapping images (21.7% vs. 22.3%, P = 0.008), the percentage of uncertain segments was lower after the addition of post-contrast T1 mapping (0.8% vs. 0.1%, P = 0.004), and the percentage of uncertain transmural extent of scarring was lower after the addition of post-contrast T1 mapping (0.9% vs. 0.1%, P = 0.001). Conclusion The addition of post-contrast T1 mapping after LGE helps to improve the detection of myocardial infarction, as well as the assessment of the transmural extent of scarring.